Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan - Pratami, Tyas Oki; Purnama, Ridwan; Widjajanta, Bambang (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
The background of this research is a low performance of the employee. It is a decline in performance appraisal results and reduced production which exceeds the tolerance limit of the company . The purpose of reasearch (1) find out the description of work environment, (2) find out the description of motivation, (3) find out the description of employee's performance, (4) find out the effect of work environment on employee's performance, (5) find out the effect of motivation on employee's performance, (6) find out the influence of work environment and motivation on employee's performance in PT. Harian Pos Kota di Jakarta. and 7) The relationship between work environment with motivation. The research is an employee's of PT. Harian Pos Kota di Jakarta. This type of research is descriptive and verification. The method in this research is random sampling with sample 175 peoples. Technical analysis of the data used in multiple linear regression with SPSS 24.0. The result of this research isÂ  employee's performance is positively influenced by work environment, employee's performance is positively influenced by the motivation, employee's performance is positively influenced by the work. environmental and motivation, and there is a positive relationship by correlation between work environment and motivation